2018
DOI: 10.1177/0907568218793517
|View full text |Cite
|
Sign up to set email alerts
|

Justifying homeschooling in Czech Republic: How “good parents” and their children use time

Abstract: In our study of Czech homeschooling families, we discovered that the unifying theme of their justifying narratives was how the families rearranged the norm of “good parenting,” defined as the amount of time families spent together. The parents argued the importance of sacrificing their own time and educating their children themselves. They distinguished themselves from parents who are not willing to attend the children’s needs as much. Finally, we show that homeschooled children also actively adopt the family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…First, this study revealed the gratitude of parents and children for the opportunity to homeschool and to be homeschooled that led to the conceptualization of homeschooling as a "gift." While homeschooling is often viewed the gift of homeschooling: adult homeschool graduates... as an act of sacrifice (Aasen, 2010;Isenberg, 2006;Lois, 2013), the current study shows that parents do not necessarily approach homeschooling as a sacrifice, where the mothers need to suppress their own needs and aspirations (Fields-Smith & Williams, 2009;Lois, 2013;Beláňová, Machovcová, & Kostelecká, 2018) but rather as an opportunity for parents to give to -as well as receive from -others: the children, the family, the community. By providing homeschooling to their children, the mothers gained transferable skills.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…First, this study revealed the gratitude of parents and children for the opportunity to homeschool and to be homeschooled that led to the conceptualization of homeschooling as a "gift." While homeschooling is often viewed the gift of homeschooling: adult homeschool graduates... as an act of sacrifice (Aasen, 2010;Isenberg, 2006;Lois, 2013), the current study shows that parents do not necessarily approach homeschooling as a sacrifice, where the mothers need to suppress their own needs and aspirations (Fields-Smith & Williams, 2009;Lois, 2013;Beláňová, Machovcová, & Kostelecká, 2018) but rather as an opportunity for parents to give to -as well as receive from -others: the children, the family, the community. By providing homeschooling to their children, the mothers gained transferable skills.…”
Section: Discussionmentioning
confidence: 63%
“…Instead, participants described their homeschooling experience as either willingly giving or gracefully receiving attention, time, skills, independence and more; often using language such as "we were able to" or "I could choose" rather than "we had to." This approach to homeschooling both challenges and complements the established image of homeschooling as a "sacrifice" (Aasen, 2010;Fields-Smith & Williams, 2009;Lois, 2013;Beláňová, Machovcová, & Kostelecká, 2018), where the parent "puts aside" her own interests and goals and focuses her time and energy fully on the children. In contrast to this view, most parents in this study highlighted the ways in which they themselves benefitted from homeschooling, namely the opportunity to spend time with and "get to know" their children well and the belief that it was more practical for them to homeschool than to enroll their children in school.…”
Section: Homeschooling As a "Gift"mentioning
confidence: 92%
See 1 more Smart Citation
“…He received homework on a day-to-day basis, so one day he had nothing to do and the other day he had a lot of work, simply too much. So, we couldn't plan his workload, do something in advance on some 2 For more information on the usual model of home education in the Czech Republic, see Beláňová at al. (2018Beláňová at al.…”
Section: Factors That Influenced Mandatory Home-based Learningmentioning
confidence: 99%
“…Murphy, Gaither a Gleim (2017) dokonce tvrdí, že snaha rodičů kontrolovat děti a jejich vzdělávání je fundamentálním motivem v rozhodnutí o domácím vzdělávání. V DV se v praxi setkáváme s tím, že rodiče vnímají předání dítěte do cizích rukou jako svým způsobem zpronevěru vůči jejich rodičovské zodpovědnosti (Beláňová, Machovcová, Kostelecká, & McCabe, 2018), silně je tak komunikován význam rodiny a zejména vztah dítěte a matky. Jakkoliv v české legislativní úpravě domácího vzdělávání zůstává příslušným institucím významná míra kontroly (např.…”
unclassified